Risk factors for post-9/11 chronic rhinosinusitis in Fire Department of the City of New York workers. Issue 12 (18th October 2018) - Putman, Barbara; Zeig-Owens, Rachel; Singh, Ankura; Hall, Charles B; Schwartz, Theresa; Webber, Mayris P; Cohen, Hillel W; Prezant, David J; Bachert, Claus; Weiden, Michael D
Abstract : Objectives: Chronic rhinosinusitis (CRS) has high socioeconomic burden but underexplored risk factors. The collapse of the World Trade Center (WTC) towers on 11 September 2001 (9/11) caused dust and smoke exposure, leading to paranasal sinus inflammation and CRS. We aim to determine which job tasks are risk factors for CRS in WTC-exposed Fire Department of the City of New York (FDNY) firefighters and emergency medical services (EMS) workers. Methods: This cohort study included a 16-year follow-up of 11 926 WTC-exposed FDNY rescue/recovery workers with data on demographics, WTC exposure, job tasks and first post-9/11 complete blood counts. Using multivariable Cox regression, we assessed the associations of WTC exposure, work assignment (firefighter/EMS), digging and rescue tasks at the WTC site and blood eosinophil counts with subsequent CRS, adjusting for potential confounders. Results: The rate of CRS was higher in firefighters than EMS (1.80/100 person-years vs 0.70/100 person-years; p<0.001). The combination of digging and rescue work was a risk factor for CRS (HR 1.54, 95% CI 1.23 to 1.94, p<0.001) independent of work assignment and WTC exposure. Conclusions: Compared with EMS, firefighters were more likely to engage in a combination of digging and rescue work, which was a risk factor for CRS. Chronic irritant exposures associated with digging and rescue work may account for higher post-9/11 CRS rates among firefighters.